The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00198-023-06748-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring barriers and opportunities to improve osteoporosis care across the acute-to-primary care interface: a qualitative study

Abstract: This qualitative study interviewed general practitioners, patients, and FLS clinicians and identified key challenges facing stakeholders seeking to improve post-fracture osteoporosis care. Local policies and care pathways as an initial strategy may address information and service delivery issues across the acute-primary care divide. Introduction Fracture liaison services (FLS) can be effective for secondary fracture prevention, but long-term adherence to therapies remains suboptimal. Few studies have explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…As an illustration of this barrier, an investigation from New South Wales, Australia, interviewed FLS clinicians, general practitioners, and patients regarding FLS programs and transitions from inpatient to primary care 31 . Because both the FLS program clinicians and primary care providers followed these patients and because communication between groups was poor, neither was certain who was responsible for longitudinal bone health.…”
Section: Barriers and Challenges For Multidisciplinary Pfcpmentioning
confidence: 99%
“…As an illustration of this barrier, an investigation from New South Wales, Australia, interviewed FLS clinicians, general practitioners, and patients regarding FLS programs and transitions from inpatient to primary care 31 . Because both the FLS program clinicians and primary care providers followed these patients and because communication between groups was poor, neither was certain who was responsible for longitudinal bone health.…”
Section: Barriers and Challenges For Multidisciplinary Pfcpmentioning
confidence: 99%
“…An analysis found that none of the 29 surveyed hospital-based programs had integrated operations with local primary care physicians, both separately from or through Primary Health Networks (27). A lack of "safety net mechanism" to monitor patients between the suspected sentinel fracture and follow-up care, and poor bi-directional communication contributed to the disjointed integration with primary care (30).…”
Section: Introductionmentioning
confidence: 99%
“…To close this gap, active engagement and integration with primary health care into secondary fracture prevention is required. There is growing consensus that most patients with osteoporosis should be managed by their primary care physician and not in capacity-limited and costly hospital-based specialist services (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…This model allows for two service configurations: a medically led, coordinated service (type A model FLS) and a GP shared-care service (type B model FLS). Despite this state-sanctioned approach, substantial variation exists in the delivery of services, both between clinics and between clinicians working within the same clinic across NSW [ 29 ]. While variation in resources probably accounts for some of the observed inter-service variation, overall there is both a lack of standardisation and a lack of consensus regarding the best approach to many aspects of care for patients after an initial FLS consultation.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care attendance patterns and long-term outcomes for these patients remain largely unknown. Nonetheless, qualitative research has identified that many factors associated with medication discontinuation and non-adherence emerge at the FLS to primary care transition, where they act as barriers to seamless post-fracture care [ 29 , 32 ]. For example, our earlier research highlighted that these can include differences in follow-up recommendations, barriers to communication, and confusion over the relative roles of primary and tertiary service providers [ 29 ].…”
Section: Introductionmentioning
confidence: 99%